Beijing genotype of Mycobacterium tuberculosis is significantly associated with human immunodeficiency virus infection and multidrug resistance in cases of tuberculous meningitis. - Caws, M; Thwaites, G; Stepniewska, K; Nguyen, T; Nguyen, T; Nguyen, T; Mai, N; Phan, MD; Tran, H; Tran, T; van Soolingen, D; Kremer, K; et al. (2006)
Multidrug-resistant tuberculous meningitis is fatal without rapid diagnosis and use of second-line therapy. It is more common in human immunodeficiency virus (HIV)-positive patients. Beijing genotype strains of Mycobacterium tuberculosis are associated with drug resistance, particularly multidrug resistance, and their prevalence is increasing worldwide. The prevalence of Beijing genotype strains among Mycobacterium tuberculosis isolates from the cerebrospinal fluid of HIV-positive (n = 35) and HIV-negative (n = 187) patients in Ho Chi Minh City was determined. The Beijing genotype was significantly associated with HIV status (odds ratio [OR] = 2.95 [95% confidence interval CI, 1.38 to 6.44]; P = 0.016), resistance to any drug (OR = 3.34 [95% CI, 1.87 to 5.95]; P < 0.001) and multidrug resistance (Fisher's exact test; P = 0.001). The association of the Beijing genotype with drug resistance was independent of HIV status. This is the first report of Beijing genotype association with HIV status, which may be an association unique to tuberculous meningitis.